The Effect of 5K2S Implementation to the Opportunities of Increasing Productivity and Workplace Improvement in PT. Andesen Jaya Plastik - Rachmatullah Rachmatullah; Tota Pirdo Kasih; Hardi Humiras Purba (ComTech: Computer, Mathematics and Engineering Applications, 2015)
The success of Japanese companies in improving productivity is because they have a culture and a high work ethic to the application of KAIZEN management system. One such application is the Cultural 5S (Seiri, Seiton, Seiso, Seiketsu, Shitsuke). In the Astra group, 5S is known as 5K2S (Order, neatness, cleanliness, sustainability Discipline, Safety, and Service). This study aims to assess the success of the application of the system 5K2S of PT. Andesen Jaya Plastik relating to opportunities for productivity. The method used isquantitative method with a descriptive study. The type of data used is primary and secondary data. While the techniques used in collecting the data are interviews, questionnaires, and literature studies. The number ofrespondents was 31 employees. Analysis of the data used is descriptive and multiple linear regression analysis. The real success rate reachs 82.24% at the stage of familiarization (effective) and they have not yet advanced tothe next stage (prevention). The response of employees is between the Agree and Strongly Agree that is 4.11 point. The correlation between 5K2S to the opportunity of significant Productivity Improvement is Seiri/Order,Seiso/neatness, and Seiketsu/Sustainability.